Management consulting. Ein neuer Weg der angewandten Sozial- und Wirtschaftsgeographie - Legoland Deutschland = Management consulting. The new way of applied social- and economic geography – LEGOLAND Germany - Klaus Kellner (Dela, 2006)
The decision of the LEGO group, to build itsfourth LEGOLAND amusement park in the Bavarian Swabian district Günzburg, has created a challenging situation for the regional politicians. With the help of the new consulting approach "Municipal Profiling", the future oriented development of the Günzburg district, was firstly clearly planned and secondly consequently enforced. The motto for the future oriented development of the district is: "District Günzburg - The Family And Children Region."